2013
DOI: 10.1007/s00268-013-2210-7
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes of Gastrectomy for Elderly Patients with Gastric Cancer

Abstract: The treatment results in elderly patients were comparable to those in nonelderly patients. These findings suggest that R0 resection with at least limited lymph node dissection according to Japanese guidelines should be considered, even for elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
79
3
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 32 publications
10
79
3
2
Order By: Relevance
“…There are several possible explanations for comparable surgical outcomes in the oldest old patients. Takeshita et al [39] reported that surgical outcomes in elderly patients were comparable to those in nonelderly patients. They suggested that the biological behavior of the tumor (e.g., tumor growth and metastatic potential) may differ between elderly and young patients.…”
Section: Discussionmentioning
confidence: 98%
“…There are several possible explanations for comparable surgical outcomes in the oldest old patients. Takeshita et al [39] reported that surgical outcomes in elderly patients were comparable to those in nonelderly patients. They suggested that the biological behavior of the tumor (e.g., tumor growth and metastatic potential) may differ between elderly and young patients.…”
Section: Discussionmentioning
confidence: 98%
“…Several authors also reported that greater blood loss during surgery is associated with an increased postoperative morbidity rate [10,11]. The amount of blood lost during surgery is directly correlated with the type of gastrectomy, extent of lymph node dissection, or combined resection of other organs; however, an inappropriate surgical maneuver such as dissection of an incorrect layer or injury to adjacent organs is also an important factor.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [11,15] from Japan also showed that overall survival after gastric cancer surgery was worse among elderly patients aged ≥80 years than among younger patients. However, these studies included patients who had undergone surgery more than 20 years ago.…”
Section: Discussionmentioning
confidence: 99%
“…The functional capacity of organs decreases with age, resulting in a decreased reserve and lower ability to endure stress (17); therefore, advanced age is a significant risk factor for increased mortality (18). However, advances in surgical and anesthesiology techniques have reportedly reduced surgical complications and have, consequently, improved the short-term surgical outcomes in elderly patients (19,20).…”
Section: Discussionmentioning
confidence: 99%